Factors Associated with Sexual Intention among Students East Kalimantan in Preventing Premarital Sexual Behavior - Wardani, Desy Ayu; Sharoni, Siti Khuzaimah Ahmad; Triyanto, Endang (Fakultas Ilmu-ilmu Kesehatan, 2025)
Sexual intention has become one of the causes of students engaging in premarital sexual behavior. This study focused on gender, relationships, self-efficacy, self-control, self-esteem, and sexual intention among students. Our research used a cross-sectional design and answered a set of questionnaires consisting of the General Self-Efficacy Scale, Self-Control Scale, the Rosenberg Self-Esteem Scale, the Youth Sexual Intention Questionnaire, and data demographic. The data were analyzed univariate and bivariate using chi-square. 328 students were included. Gender was 192 female (58.5%) and 136 male (41.5%), relationship was 69 (21%) and no having relationship was 259 (79%). The self-efficacy high was 168 (51.2%) and the low was 160 (48.8%), self-control high was 173 (52.7%), and the low was 155 (47.3%), the self-esteem high was 177 (54%) and the low was 152 (46.3%), sexual intention the high was 176 (53.7%) and the low was 152 (46.3%). Factors associated with sexual intention in preventing premarital sexual behavior were gender (p< .05), relationship (p < .05), and self-control (p < .05). Two factors that did not influence sexual intention were self-esteem (p>.05) and self-efficacy (p>.05). Gender, relationship, and self-control were an important factor associate to sexual intentions in preventing premarital sexual behavior.